Crossroads for mixed-signal chips. - Levin, P.L.
The last decade saw a surge in the number of small IC design houses, so-called fabless enterprises, that provide systems manufacturers with application-specific ICs (ASICs). More recently, shrinking circuit features and rising transistor density have spawned the system on a chip (SoC), in which most or all of the circuitry required for, say, a cellphone fits on a single IC. Today, these SoCs often contain analog, RF, and mixed-signal components to satisfy the growing demands of communication applications. SoC designers need input from the intellectual property (IP) providers that design circuit modules for use with other SoC elements. Also, they need design tools that can rapidly integrate IP libraries with the mundane sizing, placing, and routing of circuits
Keywords: ASICs; IP libraries integration; SoC designers; Circuit modules; Circuit routing; Communication applications; Fabless enterprises; Intellectual property providers; Mixed-signal chips; Small IC design houses; System on chip